(untitled) (Świat Idei i Polityki, 2009)
Gray identifies modernity as a political trend, which has reached its developed expregBion fn the Enlightenment political project, based on a rational reconstruction of morality, the idea of progress, secularization of politics and applying natural sciences methods to studying politics. The decline of the political Enlightenment, however, effected in some political disasters of the 20th century and left emptiness in the ideological space of western politics. Enlightenment project of a universal civilization demystificate not only premodern conceptions of political order, but alBO undermine itself and broke main intelectual western traditions. Political postmo- dernism, which lB answer to thifl Bituation, inherits alao some western conceptions like humanism embodied in emancipations tendencies or univeraalization of the liberal order. According to Gray’s thought, only radical attempt to theorise without typical western prejudices can be appropriate answer to late modern political and social reality.